Rail human factor training : adaptation of crew resource training in KCRC to enhance modern railway safety : a thesis presented in partial fulfilment of the requirements for the degree of Master in Aviation at Massey University, Palmerston North, New Zealand - Tsang, Tak Sum (Massey University, 2007)
Recent world headline disasters such as the September 11 attacks, 2005 London transport bombings and 2003 Daegu Subway arson attacks sent a strong warning to all nations that mass-transit systems are highly susceptible to arson or terrorist attacks with catastrophic consequences. Whilst it may be impossible to ever eliminate all forms of threats, one thing remains clear-the effectiveness of crew response to emergency situations can make a key difference between a minor incident and a full blown disaster. Staff effectiveness relies upon corporate awareness, training and investment into safety. Even a state-of-the-art system requires suitably matched and experienced staff for smooth, efficient and incident-free operation. Unfortunately, incident reports reveal consistently that about 70% of aviation and railway incidents have roots in human factors, highlighting the need to invest in effective, safety-oriented training to expose staff to operational and emergency situations in order to minimise or mitigate human error consequences. In aviation, crew resource management (CRM) was developed to address this need. CRM's effectiveness in improving teamwork, communication and staff response to emergency results in its popularity in the medical, nuclear, and military sectors. Although some work had begun to modify CRM for the railway industry, none yet existed in China or Hong Kong. Having observed the effectiveness of CRM and line oriented training (LOT) in aviation, this work documents the introduction of CRM and LOT in Hong Kong in the West Rail (WR) division of the Kowloon-Canton Railway Corporation (KCRC). One-hundred-and-twenty drivers, station and traffic controllers from WR took part in a three days CRM training program. The program used lectures, video aided training facilities (VAT) and integrated training facilities (ITF) to expose staff to CRM and safety related concepts. ITFs were used in LOT programs to simulate emergency and abnormal operation scenarios to test and train ability of teams to handle such situations. Feedback was provided by computer, video and voice records, and trainer comments. The effectiveness of the training program was tested in an emergency drill in conjunction with Hong Kong police, fire and hospital services by comparison of a control group and the CRM trained group to evaluate the program effectiveness. It was observed that the CRM group displayed better incident handling capabilities, stronger teamwork and communication throughout the exercise. When analysing incidents, CRM trained members were able to recall and consider more factors of human performance. As the instituted CRM program is still in its infancy, more time is required to prove its effectiveness. It is believed that even in this short introduction period it has raised staff awareness of safety and human factors, and improved overall teamwork and performance in WR. Now that WR serves as a knowledge portal to the rest of KCRC divisions, it is envisioned that CRM will be extended to other KCRC rails. In later years it may also broaden to intercity rails to Mainland China to improve staff performance. An effective CRM program will be the key to minimise impact and consequences if one day disaster does strike.
Keywords: Hong Kong; China; Training Employees; Railroads; Safety measures; Kowloon-Canton Railway Corporation; Teams in the workplace; West Rail Division